AV nodal reentrant tachycardia with a 2:1 right bundle branch block missed as bidirectional ventricular tachycardia in the first superficial evaluation - Akbarzadeh Mohammad Ali; Khaheshi Isa; Memaryan Mehdi; Mahjoob Mohammad Parsa; Naderian Mohammadreza (Sciendo, 2017)
A 95-year old woman was admitted to our emergency unit because of acute abdominal pain. After urgent surgery according to the acute abdomen, she was referred to intensive care unit (ICU) of the emergency unit as she was intubated. It was developed a run of new arrhythmia which was diagnosed by cardiology resident as bidirectional ventricular tachycardia due to beat to beat changing the axis of the QRS. However, a second and more precise evaluation of the abnormal ECG suggested a narrow supraventricular tachycardia, most probably AV nodal reentrant tachycardia with a 2:1 right bundle branch block.